2012
DOI: 10.2147/opth.s28623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lens status on intraocular pressure in siliconized eyes

Abstract: PurposeTo evaluate the effect of lens status on intraocular pressure (IOP) in siliconized eyes and also on the emulsification of silicone oil.Patients and methodsA total of 31 eyes of 31 patients with retinal detachment were operated on with pars plana vitrectomy and silicone oil injection: 16 phakic (Group A) and 15 pseudophakic (Group B). During the 6-month follow-up period, IOP was measured: 1 day postoperative, then at 1 week, 1 month, 2 months, 3 months, and 6 months postoperative. At the end of the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a study examining the impact of lens status on pressure values, it was noted that the group of patients with more frequent emulsification was accompanied by an increased incidence of elevated IOP. Given that the difference was statistically significant only after several weeks, the influence on IOP disturbances was suspected to be a result of chronic reaction connected to oil emulsification [25]. This is consistent with the mechanism of emulsification-it occurs over time and is therefore not responsible for sudden increases in intraocular pressure after surgery.…”
Section: Glaucoma and Increase In Intraocular Pressurementioning
confidence: 52%
See 1 more Smart Citation
“…In a study examining the impact of lens status on pressure values, it was noted that the group of patients with more frequent emulsification was accompanied by an increased incidence of elevated IOP. Given that the difference was statistically significant only after several weeks, the influence on IOP disturbances was suspected to be a result of chronic reaction connected to oil emulsification [25]. This is consistent with the mechanism of emulsification-it occurs over time and is therefore not responsible for sudden increases in intraocular pressure after surgery.…”
Section: Glaucoma and Increase In Intraocular Pressurementioning
confidence: 52%
“…The presence and type of intraocular lens seem to have an influence on the degree of oil emulsification. In a study comparing the presence of natural versus artificial lenses, pseudophakia was associated with more frequent emulsification over time (80% of pseudophakic patients compared to 19% of phakic patients) [25]. In addition to the increased frequency, the amount of emulsified oil is also significantly greater in patients after lens replacement (0.304 mm vs. 0.922 mm-UBM) [26].…”
Section: Lens Statusmentioning
confidence: 99%
“…Therefore, combined with Scleral encircling operation is a risk factor for OH after silicone oil lling. Mohalhal et al [17] found that postoperative intraocular pressure increase occurred in pseudophakic eyes. The results of this study also show that the incidence of OH after silicone oil lling in aphakic eyes is higher than that in phakic eyes.…”
Section: Discussionmentioning
confidence: 99%